Seasonal Prevalence of the Invasive Longhorn Beetle Aromia bungii in Osaka Prefecture, Japan - Yuichi Yamamoto; Shuji Kaneko (Insects, 2022)
A thorough understanding of the seasonal prevalence of invasive pests in newly invaded regions is key for establishing an appropriate and localized control plan for their successful eradication. In this study, we investigated the seasonal prevalence of the invasive longhorn beetle Aromia bungii (Coleoptera: Cerambycidae) in Osaka Prefecture, Japan. We determined the number of adult beetles sighted on host trees more than once a week from late May or early June to late August for 3 years at three study sites (one site from 2019–2021 and two sites from 2020–2021). The appearance period of A. bungii adults spanned over 2 months (June–August), and peak sighting in the field occurred in late June; the adults were more abundant in the early phase of their seasonal prevalence (around the peak dates) and almost disappeared by August. The number of adult beetles emerging from A. bungii-infested trees at one study site was surveyed daily in 2021. This survey showed a short-span adult emergence period: Approximately 1 month from the first emergence day, supporting the idea of the concentration of adult abundance in the early phase. These results will help to establish a timely pest-control plan for A. bungii in Osaka Prefecture.